Effects of interface geometry on the thermoelectric properties of laterally microstructured ZnO‐based thin films. Issue 1 (12th December 2012) - Homm, G.; Gather, F.; Kronenberger, A.; Petznick, S.; Henning, T.; Eickhoff, M.; Meyer, B. K.; Heiliger, C.; Klar, P. J.
Abstract A series of samples consisting of alternating stripes of ZnO grown by molecular‐beam epitaxy (MBE) and radio‐frequency (rf) sputtered Ga‐doped ZnO stripes was laterally microstructured with a self‐aligned pattern transfer method. We measured as a function of temperature the Seebeck coefficient S and the electrical resistivity ρ in‐plane of the samples with the transport direction perpendicular to the stripe direction. Throughout the series the bar width and hence the number of interfaces was kept constant, but the interface profile was varied yielding different interface lengths and geometries. The dependence of S, ρ and the power factor S2/ρ on the interface length at room temperature were simulated using an empirical network model and it was demonstrated that the macroscopic transport coefficients are very sensitive to the interface region and that even this rather simple modelling yields useful information about the interface region.